A bibliometric review on COVID-19 and accounting research. Issue 4 (7th December 2020) - Sarea, Adel
Abstract : Purpose: This paper is to review COVID-19 and Accounting research published during the pandemic up to July 2020. Design/methodology/approach: The study adopted bibliometric anlaysis and used the Scopus database to collect the data during the COVID-19 pandemic research published in the area of COVID-19 and accounting research. Findings: This paper has acknowledged the most relevant and scientific contributors in terms documents, institutions, sources and countries. Originality/value: To the best of the author's knowledge, this study is the first study to review COVID-19 and Accounting research agenda during the pandemic. Research limitations: This study used only articles published in journals indexed in Scopus database.